2008
DOI: 10.1007/s00213-008-1273-x
|View full text |Cite
|
Sign up to set email alerts
|

Selective phosphodiesterase inhibitors: a promising target for cognition enhancement

Abstract: Rationale One of the major complaints most people face during aging is an impairment in cognitive functioning. This has a negative impact on the quality of daily life and is even more prominent in patients suffering from neurodegenerative and psychiatric disorders including Alzheimer's disease, schizophrenia, and depression. So far, the majority of cognition enhancers are generally targeting one particular neurotransmitter system. However, recently phosphodiesterases (PDEs) have gained increased attention as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
181
0
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 253 publications
(188 citation statements)
references
References 170 publications
(287 reference statements)
4
181
0
3
Order By: Relevance
“…In addition, PDEs may be targeted for cognitive enhancement, and inhibitors of PDEs have proven to be useful experimental tools in exploring mechanisms of learning and memory Prickaerts et al, 2004). Selective PDE inhibitors of at least five types, inhibitors of PDE2 (Boess et al, 2004;Rutten et al, 2007b), PDE4 (Barad et al, 1998;Rutten et al, 2006), PDE5 (Devan et al, 2004;Rutten et al, 2005), and PDE9 (van der Staay et al, 2008) have all been shown to enhance memory in different behavioral paradigms and in different species (for review see Reneerkens et al, 2009). This study investigated the effects of PDE inhibition on spatial memory in the OLT.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, PDEs may be targeted for cognitive enhancement, and inhibitors of PDEs have proven to be useful experimental tools in exploring mechanisms of learning and memory Prickaerts et al, 2004). Selective PDE inhibitors of at least five types, inhibitors of PDE2 (Boess et al, 2004;Rutten et al, 2007b), PDE4 (Barad et al, 1998;Rutten et al, 2006), PDE5 (Devan et al, 2004;Rutten et al, 2005), and PDE9 (van der Staay et al, 2008) have all been shown to enhance memory in different behavioral paradigms and in different species (for review see Reneerkens et al, 2009). This study investigated the effects of PDE inhibition on spatial memory in the OLT.…”
Section: Discussionmentioning
confidence: 99%
“…There are 11 different families of PDEs that vary in their substrate specificity, kinetic properties, modes of regulation, intracellular localization, and tissue expression patterns (6)(7)(8). PDE 10A (PDE10A) is a dual-substrate PDE that degrades both cAMP and cGMP.…”
mentioning
confidence: 99%
“…Consistent with this hypothesis, the previous studies have demonstrated that rolipram reduces neuroinflammation and promotes axonal regeneration and functional recuperation following spinal cord injury [96][97][98]; [62]. More evidence have shown that PDE4 inhibitor rolipram reduces the production of proinflammatory cytokines and modulates the activity of cAMP-mediated signaling and thus regulates CREB phosphorylation and the downstream efectors [99]; [62,68], showing that potential PDE4 inhibitors may be suitable to antagonize psychiatric disorders. Unfortunately, the development of PDE4 inhibitor rolipram for therapeutic purposes has been hindered by side efects, such as emesis [100,101].…”
Section: Traditional Pde4 Inhibitorsmentioning
confidence: 70%